MTOR intersects antibody-inducing signals from TACI in marginal zone B cells. Issue 1 (December 2017) - Sintes, Jordi; Gentile, Maurizio; Zhang, Shuling; Garcia-Carmona, Yolanda; Magri, Giuliana; Cassis, Linda; Segura-Garzón, Daniel; Ciociola, Alessandra; Grasset, Emilie; Bascones, Sabrina; Comerma, Laura; Pybus, Marc; et al.
Abstract Mechanistic target of rapamycin (mTOR) enhances immunity in addition to orchestrating metabolism. Here we show that mTOR coordinates immunometabolic reconfiguration of marginal zone (MZ) B cells, a pre-activated lymphocyte subset that mounts antibody responses to T-cell-independent antigens through a Toll-like receptor (TLR)-amplified pathway involving transmembrane activator and CAML interactor (TACI). This receptor interacts with mTOR via the TLR adapter MyD88. The resulting mTOR activation instigates MZ B-cell proliferation, immunoglobulin G (IgG) class switching, and plasmablast differentiation through a rapamycin-sensitive pathway that integrates metabolic and antibody-inducing transcription programs, including NF-κB. Disruption of TACI–mTOR interaction by rapamycin, truncation of the MyD88-binding domain of TACI, or B-cell-conditional mTOR deficiency interrupts TACI signaling via NF-κB and cooperation with TLRs, thereby hampering IgG production to T-cell-independent antigens but not B-cell survival. Thus, mTOR drives innate-like antibody responses by linking proximal TACI signaling events with distal immunometabolic transcription programs. Marginal zone B cells differentiate into plasma cells rapidly in response to T-cell-independent antigens, but how they do so is not clear. Here the authors show TACI cooperates with TLR signalling to drive mTOR activity and subsequent class switching and plasmablast differentiation.